RESISTENSI PEDAGANG KAKI LIMA TERHADAP RAZIA SATPOL PP DI PASAR SENTRAL KOTA LAMA KENDARI - Irfan Rahmad Husain; La Ode Topo Jers; Rahmat Sewa Suraya (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2017)
This study aims to determine and to describe the form of street vendors resistance in Old City Central Market against Civil Service Police Razia. This study uses the theory of resistance. It interrelates with the object to be examined. In addition, this study also uses both ethnographic methods and data collection by using observation techniques and in-depth interviews. The informant selection technique is done by purposive sampling. The results of this study indicate that the street vendors resistance to Civil Service Police is caused by economic problems and the lack of jobs created by the Kendari City Government. This condition causes many informal sectors to try to create their own jobs by becoming street vendors, so they can meet their economic needs. However, the existence and activities of street vendors violate the Kendari City Government regarding Law No. 13 of 2008 concerning the Arrangement of Street Vendors. It tends to result in the emergence of resistance efforts from street vendors in the City towards the Perwali Law and Razia that carried out by the Civil Service Police.